2018
DOI: 10.2196/10487
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Physical Activity Program With Activity Trackers and a Mobile Phone App for Patients With Metastatic Breast Cancer: Protocol for a Single-Arm Feasibility Trial

Abstract: BackgroundAbout 5% of breast cancer cases are metastatic at diagnosis, and 20%-30% of localized breast cancer cases become secondarily metastatic. Patients frequently report many detrimental symptoms related to metastasis and treatments. The physical, biological, psychological, and clinical benefits of physical activity during treatment in patients with localized breast cancer have been demonstrated; however, limited literature exists regarding physical activity and physical activity behavior change in patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…Identifying patients suffering from sarcopenia is a first step to acknowledge the increased risk for chemotoxicity and subsequently improve and adapt supportive care of these patients. Modern tools like smartphones are already used in patients with metastatic breast cancer for implementing a personalized physical activity program (9). Use of Health Apps increases the physical activity of patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying patients suffering from sarcopenia is a first step to acknowledge the increased risk for chemotoxicity and subsequently improve and adapt supportive care of these patients. Modern tools like smartphones are already used in patients with metastatic breast cancer for implementing a personalized physical activity program (9). Use of Health Apps increases the physical activity of patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…The ABLE02 trial was based on the promising results of the ABLE single-arm trial, which highlighted the interest of patients with MBC in participating in PA interventions but also an improvement in physical fitness as well as maintenance of muscle mass, quality of life and fatigue despite the progress of the disease [20,42]. The ABLE02 trial is the first study to test the efficacy of a PA program based on connected devices (smartphone application and activity tracker) to improve HRQoL and reduce fatigue in women with MBC and to assess the effect of an intervention on other biological, psychological and functional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The ABLE pilot study showed the feasibility to use connected activity trackers to perform a 6 month-unsupervised PA program in 51 MBC patients. The results showed patients' motivation towards this program (94% acceptance rate), an improvement in physical performance as well as maintenance of PA levels, HRQoL and fatigue despite disease progression [20,42]. These promising results need to be confirmed in a large multicenter, randomized controlled study.…”
Section: Introductionmentioning
confidence: 90%
“…The proportion of participants achieving the physical activity recommendations (≥ 10.5 MET-hours/week) was not different between inclusion and the end of the study with 34 (69.4%) vs (34 (77.3%) (p = 0.26). This unsupervised physical activity program may encourage patients to maintain a long term physically active lifestyle 49 .…”
Section: Discussionmentioning
confidence: 99%